The Role of Verbal and Non-Verbal Communication in Teaching Religious Moderation - Maszeri, Maszeri; Heni Listiana; Faiqatul Munawwarah (Penerbit Hellow Pustaka, 2025)
There are two types of communication that we need to know, including individual communication and group communication which are packaged in two versions, namely verbal and non-verbal. Communication between individuals is communication that involves 2 people in conveying information or messages that are carried out verbally and non-verbally or can be said to be delivered directly (face to face), while communication between groups is communication carried out by 2 or more people verbally or non-verbally which takes place in groups that have the same goals, the same interactions and can get to know each other in placing a group. Verbal communication is a type of communication that is delivered in writing, both in terms of ideas, thoughts, decisions that are summarized in writing, listening and also reading. While the type of non-verbal communication is a type of communication that is presented without words, writing, listening or reading, the process of conveying non-verbal information through eye contact, facial expressions, body, proximity, proverbs, touch and how to dress. The method used is (library research). Literature study is a series of activities related to data collection and libraries, reading, recording and processing research materials. The results of this paper are: analyzing verbal and non-verbal communication to find out about clear, simple and easy-to-understand conversations that are all summarized and arranged in textbooks and journals to be used as guidelines in compiling and writing this work.